1996
DOI: 10.1037/h0080161
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation style and psychological functioning in children of immigrants.

Abstract: Thirty-four immigrants, predominantly Asian, and their 48 children were assessed for relationship of acculturation style to children's psychological functioning. Children of parents accepting the majority culture scored higher in social competence. Many of the children reported as having extreme behavioral problems had rejected their ethnic culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 32 publications
4
67
0
5
Order By: Relevance
“…The column labeled 'type of gap' shows that only 6 studies examined the specific role of each of the 4 types of gaps [Atzaba-Poria & Pike, 2007;Birman, 2006b;Costigan & Dokis, 2006b;Ho & Birman, 2010;Liu, Benner, Lau, & Kim, 2009;Smokowski, Rose, & Bacallao, 2008], whereas 4 studies combined all 4 types of acculturation gaps to measure whether a gap, regardless of the direction, relates to maladjustment [Crane, Ngai, Larson, & Hafen, 2005;Farver et al, 2002;Pawliuk et al, 1996;Schofield, Parke, Kim, & Coltrane, 2008]. In addition, 5 studies combined host cultural gap higher with native cultural gap lower and/or host cultural gap lower with native cultural gap higher to examine problematic mismatches in acculturation (i.e., when children acculturate to the host culture and lose their native culture at a faster pace than their parents) and benign mismatches in acculturation (i.e., when parents acculturate to the host culture and lose their native culture at a faster pace than their Chi ld > parent indicates that the child is more acculturated than the parent; child < parent indicates that the child is less acculturated than the parent.…”
Section: Four Types Of Acculturation Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…The column labeled 'type of gap' shows that only 6 studies examined the specific role of each of the 4 types of gaps [Atzaba-Poria & Pike, 2007;Birman, 2006b;Costigan & Dokis, 2006b;Ho & Birman, 2010;Liu, Benner, Lau, & Kim, 2009;Smokowski, Rose, & Bacallao, 2008], whereas 4 studies combined all 4 types of acculturation gaps to measure whether a gap, regardless of the direction, relates to maladjustment [Crane, Ngai, Larson, & Hafen, 2005;Farver et al, 2002;Pawliuk et al, 1996;Schofield, Parke, Kim, & Coltrane, 2008]. In addition, 5 studies combined host cultural gap higher with native cultural gap lower and/or host cultural gap lower with native cultural gap higher to examine problematic mismatches in acculturation (i.e., when children acculturate to the host culture and lose their native culture at a faster pace than their parents) and benign mismatches in acculturation (i.e., when parents acculturate to the host culture and lose their native culture at a faster pace than their Chi ld > parent indicates that the child is more acculturated than the parent; child < parent indicates that the child is less acculturated than the parent.…”
Section: Four Types Of Acculturation Gapsmentioning
confidence: 99%
“…This method fails to capture the variability of the different acculturation styles that are shown in table 1 . Farver et al [2002] and Pawliuk et al [1996] each computed an acculturation gap by comparing family dyads who were mismatched with those who were matched. Both studies found that mismatched dyads reported greater family conflict and youth maladjustment than matched dyads.…”
Section: Match/mismatchmentioning
confidence: 99%
“…Second, immigration itself is a stressful process, typically associated with grief, loss of family and friends, and cultural changes (Hicks et al, 1993;James, 1997), and these diverse demands may increase the vulnerability and emotional distress of migrant children (Pawliuk et al, 1996).…”
Section: The Wellbeing Of Migrant Adolescentsmentioning
confidence: 99%
“…Einen vergleichbaren Alterseffekt konnten Manassis et al (2007) (Dummit et al, 1997;Ford et al, 1998;Steinhausen & Juzi, 1996) und sechs mehrsprachig (S8, S13, S14, S15, S17 und S18). Die einsprachigen Kinder erfüllten (Calzada et al, 2009) und höheren sozialen (Pawliuk et al, 1996) sowie sprachlichen Kompetenzen (Oades-Sese & Li, 2011) einher.…”
Section: Vorhersage Der Entwicklung Des Sprechverhaltensunclassified